2016
DOI: 10.1007/s10461-016-1296-y
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Behavior and Social Network Characteristics and Functions Among Young Men Who have Sex with Men (YMSM) in Metropolitan Detroit

Abstract: HIV testing promotion is a critical HIV prevention strategy, especially among at-risk groups such as young men who have sex with men (YMSM). Based on a web survey of 194 YMSM (18–24), we examine the association of social network characteristics and functions, and of individual-level characteristics, with three HIV testing behaviors (ever, repeat, and recent testing). Network homophily was associated with recent testing in multivariable models. The network function of information acquisition was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 105 publications
(136 reference statements)
5
23
0
Order By: Relevance
“…The desire to belong to networks of similar others drives the underlying mechanism of social network homophily [21], a principle dictating that over time members of the same social network will tend to resemble one another demographically and behaviorally, with prior examples including similarities in substance use behaviors, religious beliefs, and political orientation [22]. Social network homophily has also been previously used to describe patterns in HIV risk behaviors, highlighting that members of the same social network often share similar norms, attitudes, and beliefs around HIV risk and protective behaviors [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The desire to belong to networks of similar others drives the underlying mechanism of social network homophily [21], a principle dictating that over time members of the same social network will tend to resemble one another demographically and behaviorally, with prior examples including similarities in substance use behaviors, religious beliefs, and political orientation [22]. Social network homophily has also been previously used to describe patterns in HIV risk behaviors, highlighting that members of the same social network often share similar norms, attitudes, and beliefs around HIV risk and protective behaviors [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…To inform the development of interventions to improve HIV care and PrEP engagement among YMSM, a growing number of studies have reported the barriers and facilitators YMSM report they encounter when accessing HIV treatment or prevention services. [7][8][9][10][11][12][13][14] While important insights can be gained from the analysis and reporting of each barrier and facilitator individually, additional information can emerge when they are collectively viewed as positioned within a larger theoretical context.…”
Section: Introductionmentioning
confidence: 99%
“…Policy makers should commission further research to expand the findings of this study and better understand the way in which expatriate and traveler networks function (both online and offline), specifically the cohesion, density, and homophily of networks [ 87 , 88 ]. A social network analysis within and between forums would complement our findings.…”
Section: Discussionmentioning
confidence: 99%